THE DEVELOPMENT OF GUIDED INQUIRY-BASED STUDENTS WORKSHEET TO INCREASE CRITICAL THINKING SKILLS OF SENIOR HIGH SCHOOL STUDENTS - KURNIA OKTAVERINA, ELLA; , MADLAZIM (Inovasi Pendidikan Fisika, 2018)
Student worksheet is procedural sheets which are often used in learning as guide in the form of tasks or activities undertaken by learners. Besides, guided inquiry is learning model which aims to give space for the students so they are able to construct their thinking skills, one of them is critical thinking skill. This study aims to (i) determine the validity of guided inquiry based student worksheet to increase the students? critical thinking skills, (ii) determine the practicality of guided inquiry based student worksheet to increase the students? critical thinking skills, and (iii) determine the effectiveness of guided inquiry based student worksheet to increase the students? critical thinking skills. This study is a development study using ADDIE Model (Analysis, Design, Development, Implementation, Evaluation) with subject of trial as many as 24 students in 10th science class, Senior High School 1 Sampang. From this study, it was found that (i) guided inquiry based student worksheet to increase critical thinking skills that has been developed is very valid to be used in learning with percentage in general 86,1%, (ii) the student worksheet is practical in terms of the learning activities result and the students? activities with percentages respectively 90,6% and 84,5%, and (iii) student worksheet which has been developed is effective in terms of critical thinking skills test result with n-gain score 0,78 which belongs to high category and the students? responses with average percentage 88,6%. Keywords: Student worksheet, Guided Inquiry, Critical Thinking Skills.